Analisis Laporan Keuangan Pada Usaha Mikro, Kecil, Dan Menengah Yang Ada Di Kota Ambon - Tiara Tiara; Jeclin Huwae; Rizal M Tanassy; Masita Latupono; Bryan Pelo (Asosiasi Riset Ekonomi dan Akuntansi Indonesia, 2023)
This study aims to provide an overview of the preparation of financial statements for MSMEs. This research takes the object of the Groceries business (Ica Kiosk) which was founded in 2018, and is located in Mardika, Rijali Village, Ambon City. Data collection is done through interviews. The results of the study show that the financial reports made are still not in accordance with SAK. Then, the information contained in financial reports is still simple and still financial from practitioners. The obstacles faced by owners in making financial reports are the lack of time allocation they have and the assumption that making financial reports is complicated and difficult for owners to understand.